A duplication cyst masquerading as a meckel's diverticulum. (24th May 2012) - Wheatley, KE; Jayatunga, R; Singh, M; Gardiner, CE
Abstract : Gastrointestinal tract duplication cysts are rare congenital malformations, usually presenting in infancy or early childhood with a variety of symptoms within the GI tract. Sources of GI bleeding can present a diagnostic dilemma despite conventional radiological & endoscopic investigations. We present an unusual case of a 13 year old boy, who presented with an acute abdomen and malaena with contrasting radiological and operative findings. A 13 year old boy was referred to our hospital with a 2 week history of severe central abdominal pain and 2 episodes of malaena. On assessment he appeared well and was haemodynamically stable. On physical examination his abdomen was tender centrally. Digital rectal examination was normal. Blood tests revealed a Haemoglobin of 7.2 with a MCV of 58.3. Abdominal X-ray showed faecal loading. An ultrasound scan of his abdomen found an abnormally dilated fluid-filled loop in the right iliac fossa extending into the pelvis. An MRI scan with Haste sequences was undertaken for additional clarity, and this favoured a Meckel's appearance. A laparotomy revealed a large 30 cm long cystic lesion in the mesentery of the ileum. The ileum was extremely adherent to this cyst, thus en bloc ileal resection was performed with primary anastomosis. The boy was discharged uneventfully on post-operative day 3. Histology confirmed a congenital duplication cyst with heterotopic gastric glands. This demonstrated an area of haemorrhage subserosally. Alimentary tract duplications are rare childhood anomalies, but may cause intestinal obstruction, intussusception, haemorrhage or perforation. They are most commonly located in the ileum, but can occur anywhere from pharynx to rectum. They are lined by intestinal tract mucosa and share a common smooth muscle wall and blood supply with adjacent bowel wall, with which they can communicate. Malignant change has rarely been reported in adults, in particular within rectal duplication cysts. The duplication cyst attached to this boy's ileum revealed gastric mucosa, which contains acid-secreting parietal cells resulting in peptic-ulcer type ulceration and bleeding. Intestinal duplication cysts should be considered in the differential diagnosis of GI bleeding in children. Complete excision is the treatment of choice.